Performance assessments of the middle and late phase of rehabilitation following lower limb injury in professional rugby union players - McCarthy-Ryan, M. F.; Mellalieu, S.; Bruton, A.; Moore, I. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to characterise the kinetic profile of the jumping strategy employed in rugby union players during the middle and late phases of rehabilitation following lower limb injury. Nine players from a professional rugby union team (height 1.80±0.06 m; mass 96.1±13.2 kg; age 25±3 years) were included in this study. The mean duration of the middle and late phases of rehabilitation were 10±5 weeks and 6±2 weeks respectively. Unilateral drop jump and unilateral lateral hurdle hop were used to characterise the middle and late phases respectively. The variables of interest were Initial peak landing force, ground contact time, net impulse, Instantaneous loading rate, flight time and second peak landing force. Differences were observed in kinetic jump profiles between uniplanar and multiplanar movements. A change in kinetic jumping strategy to attain the same performance magnitudes across both phases of rehabilitation was also observed. The results highlight the importance of practitioners using a range of functional assessments in return to play testing.